2003
DOI: 10.1039/b201455f
|View full text |Cite
|
Sign up to set email alerts
|

Toggling enantioselective catalysis—a promising paradigm in the development of more efficient and versatile enantioselective synthetic methodologies

Abstract: The increasingly needed synthesis of both enantiomers of a chiral compound usually requires the use of both enantiomers of a chiral catalyst. Several of the usually employed chiral ligands are naturally available in only one enantiomeric form, the antipode often being of labor-intensive preparation. Enantiodivergent asymmetric catalysis has accrued in importance in this regard, in that it allows expeditious access to both enantiomers of a product without any direct modification on the chemical structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(56 citation statements)
references
References 34 publications
(36 reference statements)
0
55
0
Order By: Relevance
“…Similar effects have been reported in other papers and are known as 'dual stereocontrol'. 10,11 Furthermore, in the case of the indane-fused oxazolines 6aA and 14, increasing the steric bulk of the tether resulted in a lower enantioselectivity. In contrast, when the chiral substituent on the oxazoline moiety was a t-butyl-substituent, higher enantioselectivities were obtained with a bulky phenyl-substituted tether.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects have been reported in other papers and are known as 'dual stereocontrol'. 10,11 Furthermore, in the case of the indane-fused oxazolines 6aA and 14, increasing the steric bulk of the tether resulted in a lower enantioselectivity. In contrast, when the chiral substituent on the oxazoline moiety was a t-butyl-substituent, higher enantioselectivities were obtained with a bulky phenyl-substituted tether.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…5a This effect, together with the dual stereocontrol, suggests that the introduction of the phenyl substituents modifies the catalytic mechanism or the structure of the catalytic site. 10,11 3. Conclusion…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…[6] Many of the generally used chiral ligands are naturally available in only one enantiomer; the other enantiomer often requires a labor-intensive preparation. The importance of enantioselective catalysis has increased in this regard, as it allows easy access to both enantiomers of a product without any complex modification of the structure of the chiral promoter.…”
mentioning
confidence: 99%
“…[4] The successful application of these ligand systems motivated us to screen the Nozaki-Hiyama allylation of aromatic aldehydes. Initial evaluation of symmetrical (4)(5)(6) and non-symmetrical bipyridine ligands (1)(2)(3) in the Cr(II)-catalyzed addition of allyl halides to benzaldehyde revealed that C 2 -symmetrical Configuration [4a] To increase the applicability of the ligand system, the enantiomer 4a of ligand 4 was synthesized from (À)-b-pinene according to the synthetic protocol for ligand 4 ( Figure 1). An X-ray crystallographic analysis of (+)-6 ( Figure 2) verified the general structure of these tetradentate N 2 O 2 ligands, [5] which have features that resemble those of the well known Jacobsen salen ligand and TADDOL.…”
mentioning
confidence: 99%
“…We surveyed tert-butyl carbamate, tert-butyl carbazate, and aniline (Table 3); in all cases, the opposite enantiomer of the allylic amine analogue was produced as the major product relative to the hydroazidation reaction. Enantiodivergence in synthetic protocols has previously been reported, [23] and is usually brought about by modification of various reaction parameters, including catalyst identity (e.g. changes to metal or ligand), temperature, solvent, and additives, among others.…”
mentioning
confidence: 99%